Parison Of Health Education Effectiveness Through Poster And Vodeo Media On Improvement Of Climacterium Mother Knowledge In Facing Menopouse - Yulli Fety; La Rangki; Ananda Safitri (Jurnal Inspirasi Kesehatan, 2023)
Background: Increased health status has in impact on the age of women which causes the number of menopause women to also increase. In wundudopi sub district, Kendari city, there are 2.055 women. When entering menopause women will be faced with a new problem that is the change in the body’s metabolism. Purpose: This research is aims to compare the effectiveness of health education through poster and video media on improvement of climacterium mother knowledge in facing menopause in wundudopi sub district in Kendari city. Method: The type og this research uses a quasi-experimental method by comparing counseling knowledge groups through poster and video. The sample in this research was 34 women in wundudopi sub-district. Data collected by measuring knowledge using a questionnaire pre and posttest counseling and statistical analysis paired at a 95% confidence level with α = 0.05. Result: The finding of paired and independent data t-tes conducted that the provision of health education through poster media to increase knowledge with t=14.503 with sig 0.000<0.005 health education trough video media t=2.257 with sig 0.000<0.05. And there are differences in the knowledge of health education through poster and video media before and after counseling t= 15.993 with sig 0.000<0.05. Conclusion: This research concluded that there is a comparison of the effectiveness of health education through poster and video media on the increased knowledge of climacterium mother in the face of menopause in the wundudopi sub-district of Kendari city.